Nitric Oxide Mediated Transcriptome Profiling Reveals Activation of Multiple Regulatory Pathways in Arabidopsis thaliana - Hussain, Adil; Mun, Bong-Gyu; Imran, Qari M.; Lee, Sang-Uk; Adamu, Teferi A.; Shahid, Muhammad; Kim, Kyung-Min; Yun, Byung-Wook (Frontiers in Plant Science, 2016)
Imbalance between the accumulation and removal of nitric oxide and its derivatives is a challenge faced by all plants at the cellular level, and is especially important under stress conditions. Exposure of plants to various biotic and abiotic stresses causes rapid changes in cellular redox tone potentiated by the rise in reactive nitrogen species that serve as signaling molecules in mediating defensive responses. To understand mechanisms mediated by these signaling molecules, we performed a large-scale analysis of the Arabidopsis transcriptome induced by nitrosative stress. We generated an average of 84 and 91 million reads from three replicates each of control and 1 mM S-nitrosocysteine (CysNO)-infiltrated Arabidopsis leaf samples, respectively. After alignment, more than 95% of all reads successfully mapped to the reference and 32,535 genes and 55,682 transcripts were obtained. CysNO infiltration caused differential expression of 6,436 genes (3,448 up-regulated and 2,988 down-regulated) and 6,214 transcripts (3,335 up-regulated and 2,879 down-regulated) 6 h post-infiltration. These differentially expressed genes were found to be involved in key physiological processes, including plant defense against various biotic and abiotic stresses, hormone signaling, and other developmental processes. After quantile normalization of the FPKM values followed by student’s T-test (P<0.05) we identified 1,165 DEGs (463 up-regulated and 702 down-regulated) with at least 2-folds change in expression after CysNO treatment. Expression patterns of selected genes involved in various biological pathways were verified using quantitative real-time PCR. This study provides comprehensive information about plant responses to nitrosative stress at transcript level and would prove helpful in understanding and incorporating mechanisms associated with nitrosative stress responses in plants.